Anti-hypercholesterolemic activity of standardized fermented Allium cepa L. var aggregatum extract: In vitro and in vivo studies - Ade Sri Rohani; Yuandani Yuandani; Panal Sitorus; Dimas Andrianto; Aminah Dalimunthe (Shahrekord University of Medical Sciences, 2022)
Introduction: Allium cepa extract has been reported to have anti-hypercholesterolemic activity in rats. This study was conducted to investigate the effects of standardized fermented A. cepa L. var aggregatum extract on cholesterol levels and HMG-CoA reductase enzyme. Methods: The fermented A. cepa extract was standardized by the presence of quercetin using a validated high performance liquid chromatography (HPLC) method. The activity of the extract on HMG-CoA reductase was determined using HMG-CoA Assay kits, then measured by Nano spectrophotometry. In vivo study was conducted in hypercholesterolemic rats. The extract was administered orally at doses of 100, 200, and 300 mg/kg body weight (bw) to rats for 21 days and the cholesterol levels were measured every week. Results: All doses of fermented A. cepa extract and its marker compound, quercetin, ameliorated the levels of high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) as compared to those of negative control (P<0.05). Of all the doses, fermented A. cepa extract at the dose of 200 mg/kg bw displayed the highest reduction in LDL-C levels. In addition, the extract at the dose of 200 mg/kg bw showed the strongest enhancement in HDL-C levels. The fermented A. cepa extract and quercetin also inhibited the HMG-CoA reductase enzyme with inhibitory activity of 61.78%. Conclusion: The ethanol extract of fermented A. cepa shows anti-hypercholesterolemic activity. The strong anti-hypercholesterolemic activity of the extract might be due to the high amounts of quercetin, although other constituents may also contribute.